In a Randomized, Placebo-Controlled Cross-Over Study, Administration of 6 and 12 G Fortetropin® Does Not Reduce Serum Myostatin in Healthy Adult Dogs Over 72-Hours - Nugent Britt, Carmella C.; Alvarez, Leilani X.; Lamb, Kenneth (Frontiers in Veterinary Science, 2021)
The objective of this study was to evaluate the effect of a single administration of 6 g and 12 g of Fortetropin compared to placebo on serum myostatin in dogs over a 72-hour period. Ten hospital-employee-owned healthy adult dogs aged 2 to 8 years old were enrolled in the study. In this prospective, randomized, double-blind, crossover study, blood samples were collected prior to and then 12, 24, 36, 48, and 72 hours following administration of the test agent or placebo. Serum samples were processed according to manufacturer’s guidelines for canine serum using GDF-8/Myostatin Quantikine ELISA kit (R&D Systems). Analysis-of-variance (ANOVA) analyses were carried out where P < .05 was deemed significant. Mean serum myostatin was not significantly lower in treatment groups compared to placebo at any time point. Baseline mean serum myostatin in low and high dose treatment groups was 29,481 (SD = 5,224) and 32,214 pg/mL (SD = 7,353) respectively. Baseline mean serum myostatin in low and high dose placebo groups was 30,247 (SD =5,875) and 28,512 (SD = 5,028). The results of this study do not support that a single dose of Fortetropin reduces serum myostatin in healthy adult dogs. Further studies are recommended to determine the efficacy and bioavailability of Fortetropin in dogs.